Power effects, normalising advice and evolving knowledge of doctoral writing - Gormley, Kevin; Mochizuki, Naoko (Discourse and Writing/Rédactologie, 2023)
Prescriptive advice about doctoral writing often fails to recognise the complexities of the doctoral journey. Linguistic and cultural backgrounds are negated where advice about writing converges around a norm. In this paper, we explore the role of ‘advice’ in our growth as thesis writers by examining our literacy history and tensions we faced while writing our theses. We pursue a duoethnographic process (Sawyer & Norris, 2013), a process that facilitates the construction and reconstruction of perspectives. From our differing backgrounds, we experienced discourses of ‘advice’ in alternative ways. We identify opposing 'advice' trends which, in turn, provided a space for our agency. Inspired by Foucault’s (1977) ‘power/knowledge’ we think of past experiences and encounters along our doctoral journey as power effects which shaped our views on advice. We conclude by outlining how insights for our teacher-selves inform how we speak about impacts and advice with doctoral students.